Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/dcr.0000000000001198
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital and Surgeon Volume and Rectal Cancer Surgery Outcomes in Patients With Rectal Cancer Treated Since 2000: Systematic Literature Review and Meta-analysis

Abstract: Background: Previous reviews and meta-analyses, which predominantly focused on patients treated before 2000, have reported conflicting evidence about the association between hospital/ surgeon volume and rectal cancer outcomes. Given advances in rectal cancer resection such as total mesorectal excision, it is essential to determine if volume plays a role in rectal cancer outcomes among patients treated since 2000. Objective: Determine if there is an association between hospital/surgeon volume and rectal cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 48 publications
1
51
0
4
Order By: Relevance
“…Finally, the difference may be related to the experience of the two highly specialized complex pelvic surgery centres in Australia compared with ten specialized colorectal centres in France, with only a few specialized in complex pelvic surgery. It has been shown that centralization of rectal cancer surgery improves outcomes [20][21][22] . This last argument is supported by the wide variation in R0 resection rates for LRRC from 46 to 68 per cent in French centres according to the number of patients treated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the difference may be related to the experience of the two highly specialized complex pelvic surgery centres in Australia compared with ten specialized colorectal centres in France, with only a few specialized in complex pelvic surgery. It has been shown that centralization of rectal cancer surgery improves outcomes [20][21][22] . This last argument is supported by the wide variation in R0 resection rates for LRRC from 46 to 68 per cent in French centres according to the number of patients treated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the definition of hospital volume was heterogeneous and the number of pooled patients was relatively low. A systematic review and meta‐analysis of 45 275 patients with rectal cancer treated within a multimodal setting showed reduced postoperative mortality for those treated in high‐volume hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect sizes are small, it is a non-linear effect and the definition of high hospital volume is heterogenic between different studies. This makes it hard to define a clear threshold for minimum annual number of colorectal cancer surgeries per hospital 20–24. Also, a difference between US and non-US data suggests that hospital level variability was less of a problem outside the USA than in the USA 20 24.…”
Section: Discussionmentioning
confidence: 99%